2018
DOI: 10.1002/er.4005
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of interfacial thermal stresses of solid oxide fuel cell applied for submarine power

Abstract: Summary Solid oxide fuel cell (SOFC) due to its high energy conversion rate and low noise can replace diesel energy as the submarine power. The interface thermal stress has an important effect on the stabilization and endurance of SOFC. The thermomechanical model of SOFC, which takes the interfacial layer into account, is developed to analyze the interfacial thermal stresses between electrodes and electrolyte in this paper. Based on the formation mechanism and composition distribution of the interfacial layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 45 publications
(93 reference statements)
0
12
0
Order By: Relevance
“…Substituting Equations (20) and (21) into Equation (19) gives the displacement equations in terms of Young's modulus as follows, respectively 28 :…”
Section: Navier Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…Substituting Equations (20) and (21) into Equation (19) gives the displacement equations in terms of Young's modulus as follows, respectively 28 :…”
Section: Navier Equationmentioning
confidence: 99%
“…19 Xie et al determined the material property of the interfacial layer based on the formation mechanism and composition distribution of the interfacial layer, and the analytical solutions of interfacial thermal stresses including both shear stress and peel stress between the electrodes and electrolyte of SOFC are deduced. 20 Wang et al described the temperature profile according to measured temperature points in the stack. It can be clearly seen that the maximum stress concentration area appears at the corner of the components when the stack is heated from room temperature 800 C. The effects of stack components on maximum stress concentration have been investigated under the operation temperature, as well as the thermal stress simulation results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the change of temperature and mismatching mechanical properties, multiple stresses exist within the cell, and delamination and transgranular fracture are the two main failure modes of the cell. Xie et al took the interfacial layer into account in their thermomechanical model. They analyzed the interfacial thermal stresses between the electrodes and the electrolyte and found that anode's interface stress level is higher than that of cathode's interface.…”
Section: Introductionmentioning
confidence: 99%
“…If the mechanical performance of a battery pack casing cannot meet the requirements of real application, it may result in the short circuit even explosion or more severe accidents . Therefore, the mechanical performance of a battery pack casing is significant for batteries, electric vehicles, and road safety . In addition, lightweight is also considered as an objective which is necessary for less volume consumption and more extended driving range.…”
Section: Introductionmentioning
confidence: 99%